Age, Export Orientation and Technical Efficiency: Evidence From Garment Firms in DKI Jakarta - Walujadi, Dedi (Makara Human Behavior Studies in Asia, 2004)
In this paper, the technical efficiency of garment firms in DKI Jakarta is estimated by incorporating a model for the technical inefficiency effects in the stochastic frontier production function. The aims are to estimate both the technical efficiency of the firms and the sources of technical inefficiency within the context of Indonesia’s macro-economic policy. The empirical results point a number of noteworthy features of the economic performance of firms in relation with some specific characteristics. It is found in the study that the Cobb douglas functional form was not adequate, but the sources of technical inefficiency were found and technical change was present.